2015
DOI: 10.1007/s12032-015-0531-0
|View full text |Cite
|
Sign up to set email alerts
|

CCR9–CCL25 interaction suppresses apoptosis of lung cancer cells by activating the PI3K/Akt pathway

Abstract: CC chemokine receptor-9 (CCR9) is highly expressed in non-small cell lung cancer (NSCLC) tissues and cell lines. However, the biological functions and the signals elicited by the interaction between CCR9 and its natural ligand CCL25 in NSCLC are unknown. Here, we selectively depleted CCR9 and inhibited CCR9-CCL25 interaction in NSCLC cells using small recombinant lentivirus-mediated miRNA, and investigated the tumorigenic effects in vitro and in vivo. Compromised CCR9-CCL25 interaction promoted apoptosis in NS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 33 publications
(40 reference statements)
1
31
0
Order By: Relevance
“…These included two chemokine receptors (CCR), CCR9 and CCR2, which have been implicated in driving oncogenesis and shown to induce apoptosis when depleted in cancerous cells [28, 29], Testis expressed 14 (TEX14) that is a PLK1 regulated protein [30], as well as Wnt inhibitory factor 1 (WIF1), which antagonises Wnt signaling [31] and may therefore be important for the control of the pathway in ovarian cancer cells. In addition, Three enzymes with roles in metabolism were identified from the screen as causing a significant fold decrease in the number of mitotically arrested cells following paclitaxel treatment after their depletion, two of which were more directly linked to glycolysis; XYLB and PFKFB4.…”
Section: Resultsmentioning
confidence: 99%
“…These included two chemokine receptors (CCR), CCR9 and CCR2, which have been implicated in driving oncogenesis and shown to induce apoptosis when depleted in cancerous cells [28, 29], Testis expressed 14 (TEX14) that is a PLK1 regulated protein [30], as well as Wnt inhibitory factor 1 (WIF1), which antagonises Wnt signaling [31] and may therefore be important for the control of the pathway in ovarian cancer cells. In addition, Three enzymes with roles in metabolism were identified from the screen as causing a significant fold decrease in the number of mitotically arrested cells following paclitaxel treatment after their depletion, two of which were more directly linked to glycolysis; XYLB and PFKFB4.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous previous studies have also studied the essential effects of CCR9 on the AKT signaling pathway and related diseases. Li and coworkers 29 found that compromised CCR9-CCL25 interactions promoted apoptosis in non-small cell lung cancer cells by activating phosphatidylinositol 3 kinase/AKT in vitro, which resulted in the upregulation of antiapoptotic proteins and downregulation of apoptotic proteins. In addition, the results of breast cancer-related research demonstrated that the CCR9-CCL25 axis activates cell survival signals through AKT and subsequent GSK3b inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was consistent with our previous experimental result that CCR9 is up-regulated in NSCLC compared with adjacent normal lung tissue at the transcriptional level [ 10 ]. Previously, we have also shown that over-expressed CCR9 interacts with CCL25 to promote proliferation and suppress apoptosis of NSCLC cells in vitro , and knockdown of CCR9 compromises in vivo tumor growth in a nude mice model [ 11 ]. These observations demonstrated that like other members of the CC chemokine receptor family [ 13 ], CCR9 may function as an oncogene and play an important role in the tumorigenesis and development of lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we observed a clear trend between CCR9 expression and pathologic differentiation, although this trend was not significant (p = 0.225). In the previous study, we have found that CCR9-CCL25 axis plays a significant role in survival of NSCLC cells by inhibiting cancer cell apoptosis both in vitro and in vivio through the activation of PI3K/Akt signaling pathway, and cell survival is essential for cancer cells to achieve invasion and metastasis [ 11 ]. Therefore, over-expression of CCR9 in lung adenocarcinoma suggested its crucial role in disseminating primary tumor and promoting tumor cell survival during metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation